2007 IEEE International Conference on Ultra-Wideband 2007
DOI: 10.1109/icuwb.2007.4381027
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of an IEEE 802.15.4a Physical Layer with Energy Detection and Multi-User Interference

Abstract: Abstract-We evaluate the performance of an IEEE 802.15.4a ultra-wide band (UWB) physical layer, with an energy-detection receiver, in the presence of multi-user interference (MUI). A complete packet based system is considered. We take into account packet detection and timing acquisition, the estimation of the power delay profile of the channel, and the recovery of the encoded payload. Energy detectors are known to have a low implementation complexity and to allow for avoiding the complex channel estimation nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 14 publications
(21 reference statements)
0
34
0
Order By: Relevance
“…For packet detection, PICNIC uses a correlation-based packet detection algorithm as in [11] and [16]. However, the novelty of PICNIC and its robustness to interference rely on 1) a preprocessing prior to the correlation of the received signal using thresholding and 2) a postprocessing of the correlation output with an interference detection and cancellation mechanism.…”
Section: ) Summary Of Our Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For packet detection, PICNIC uses a correlation-based packet detection algorithm as in [11] and [16]. However, the novelty of PICNIC and its robustness to interference rely on 1) a preprocessing prior to the correlation of the received signal using thresholding and 2) a postprocessing of the correlation output with an interference detection and cancellation mechanism.…”
Section: ) Summary Of Our Contributionsmentioning
confidence: 99%
“…And not accounting for MUI with an ED architecture can greatly degrade system performance, even at low data-rates [11], [12]. One option to prevent MUI is to coordinate medium access, for instance, with carrier sensing.…”
mentioning
confidence: 99%
“…In near-far cases (the additional transmitters have 10dB higher power), there is still a significant performance increase compared to the worst case "Destructive Collisions" curve. Note that with a conventional receiver where no thresholding is done, the near-far cases correspond to the "Destructive Collisions" curve already at a lower rate of λ = 10 pkts/s [4].…”
Section: Permentioning
confidence: 99%
“…In [4], the performance of an IEEE 802.15.4a compliant energy-detection receiver is analyzed in the presence of several transmitters using an Aloha medium access control (MAC)…”
Section: Introductionmentioning
confidence: 99%
“…The available literatures in this area have already analyzed the system performance in the presence of narrowband interference, multiuser interference, and multipath interference [3][4][5][6][7][8]. Reference [3] and [4] mainly discussed multiuser interference and proposed the energy-detection receiver and non-linear filtering approach to mitigate such interference. Reference [5] mainly investigated the system performance of IR-UWB with narrow band interference (NBI) and concluded that NBI will greatly worsen system performance.…”
Section: Introductionmentioning
confidence: 99%